A New Era in Ocular Therapeutics: Advanced Drug Delivery Systems for Uveitis and Neuro-Ophthalmologic Conditions - Kevin Y. Wu; Kenneth Tan; Dania Akbar; Mazen Y. Choulakian; Simon D. Tran (MDPI AG, 2023)
The eye's intricate anatomical barriers pose significant challenges to the penetration, residence time, and bioavailability of topically applied medications, particularly in managing uveitis and neuro-ophthalmologic conditions. Addressing this issue, polymeric nano-based drug delivery systems (DDS) have surfaced as a promising solution. These systems enhance drug bioavailability in hard-to-reach target tissues, extend residence time within ocular tissues, and utilize biodegradable and nanosized polymers to reduce undesirable side effects. Thus, they have stimulated substantial interest in crafting innovative treatments for uveitis and neuro-ophthalmologic diseases. This review provides a comprehensive exploration of polymeric nano-based DDS used for managing these conditions. We discuss the present therapeutic hurdles posed by these diseases and explore the potential role of various biopolymers in broadening our treatment repertoire. Our study incorporates a detailed literature review of preclinical and clinical studies from 2017 to 2023. Owing to advancements in polymer science, ocular DDS has made rapid strides, showing tremendous potential to revolutionize the treatment of patients with uveitis and neuro-ophthalmologic disorders.